Hubungan Motivasi Orang Tua dengan Hasil Belajar Siswa pada Mata Pelajaran Geografi - Handelia Mawi; Kalvin Salindeho Andaria; Hilda Vemy Oroh (Jurusan Pendidikan Geografi Universitas Negeri Manado, 2022)
The purpose of this study is to ascertain the connection between parental motivation and academic accomplishment. The research technique employed is a quantitative correlation method. strategies for gathering data include observation, interviews, questionnaires, and documentation. The t test and product moment correlation test are both used in the analysis technique. The results demonstrated that parental motivation had an impact on students' learning outcomes at SMA Negeri 3 Tana Toraja in geography as indicated by tcount = 31,854 > ttable 2,015, and the determinant coefficient was 85%, meaning that parental motivational variables accounted for 85% of the variance in students' learning outcomes and that the remaining 15% was influenced by other factors. Parental motivation is a strong predictor of student learning results. Parents' behavior is adequate to inspire youngsters to engage in learning activities